Low-risk gestational trophoblastic neoplasia: A single-center experience from Saudi Arabia - Abdulaziz Alobaid (Thieme Medical and Scientific Publishers Pvt. Ltd., 2019)
Objective: To report our single-center experience in terms of patient clinical characteristics, treatment outcomes, and chemotherapy-related toxicities in patients with low-risk gestational trophoblastic neoplasia (GTN). Materials and Methods: A retrospective cross-sectional study (2008–2013) was conducted at a tertiary health-care hospital in Saudi Arabia. Forty-four (n = 44) patients met the inclusion criteria for low-risk GTN. Methotrexate (MTX) was administered in a 5-day regimen: 0.3–0.5mg/kg intravenously (IV) daily for 5 days every 2 weeks (maximum 25mg per dose). Actinomycin D (ActD) was administered 1.25mg/m2 pulsed IV every 2 weeks. Results: The majority of patients had molar pregnancy as the antecedent event (86%), developed GTN within the first 4 months after the initial evacuation (93.2%), had human chorionic gonadotropin levels between 1,000 and 10,000 mIU/dL (36.3%), and had the World Health Organization prognostic scores from 0 to 2 (48.7%). Only 38 patients accepted treatment with chemotherapy. A total of 37 patients received first-line MTX; 34 patients of them achieved complete remission (CR, 92%). The three patients who developed MTX resistance were salvaged with sequential ActD and all achieved CR of 100%. Only one patient received first-line ActD and achieved CR. The overall survival as well as cure rate for all patients with low-risk GTN was 100%. No patient developed MTX-related hepatic toxicity or ActD-related blister formation. No severe adverse effects occurred. Conclusion: Our 5-day IV MTX regimen was highly effective in treating patients with low-risk GTN, with CR rate of 92% and no severe toxicity. Primary and sequential ActD therapy appears to be very effective.